Effects of different pre-conditioning exercise on leptin synthesis and its downstream signalling pathway in T2DM rats - Sen Lin; Yuzhi Hu; Shuqiao Ding; Yazhe Hu (Iranian Journal of Basic Medical Sciences)
Objective(s): This study aimed to evaluate the effects of pre-conditioning exercise on body lipid metabolism, leptin secretion, and the downstream pathways at the early stage of type 2 diabetes mellitus (T2DM).Materials and Methods: The T2DM model was established using an 8-week high-sugar, high-fat diet combined. The T2DM model was established using an 8-week high-sugar, high-fat diet combined with streptozocin (STZ) injection. Two exercise interventions, high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) were performed during the model-building process. One week following the STZ injection, rats were euthanized. Blood, gastrocnemius muscle, and epididymal fat pad were collected. Plasma leptin content was measured by ELISA. The expression of leptin-mRNA in epididymal adipose tissue was measured using RT-qPCR, and its protein expression was detected by a western blot. Leptin, leptin-R, and AMPK (AMP-activated protein kinase) - ACC (Acetyl-CoA carboxylase) expression in gastrocnemius muscle was also detected by western blot. Free fatty acids (FFA) and triglycerides (TG) contents in gastrocnemius muscle were measured using a biochemical assay.Results: In the HIIT group, glucose tolerance and leptin receptor expression increased, as did the expression and phosphorylation of AMPK protein. At the early stage of T2DM, it increased significantly in the gastrocnemius muscle in the MICT group.Conclusion: At the early stage of T2DM, pre-conditioning exercise in the form of HIIT was found to inhibit the leptin-mRNA expression in adipose tissue, suppress leptin synthesis, up-regulate AMPK-ACC signaling pathway, and promote lipid decomposition in skeletal muscle tissue. Pre-conditioning of MICT led to the accumulation of FFA and TG in skeletal muscle, likely due to exercise adaptation rather than ectopic deposition of lipids.